Visual Acuity alterations in heavily impaired Congenital Zika Syndrome (CZS) children - Baran, Luiz C. P.; Lima, Diego da S.; Silva, Leonardo A.; Tabares, Heydi S.; Dias, Sarah L.; Zin, Andrea Araújo; Moreira, Maria E. L.; da Costa, Marcelo F.; Ventura, Dora F. (Frontiers in Ophthalmology, 2022)
We aim to assess visual acuity (VA) in Congenital Zika Syndrome (CZS)-children to evaluate visual loss. To that end we evaluated 41 CSZ- children, from Rio de Janeiro using Teller Acuity Cards. They had Zika virus-infection confirmed by reverse transcription–polymerase chain reaction (RT-PCR) or clinical evaluation. VA below normative values was present in 39/41 (95%). In 10 cases, VA was only marginally below normal; in the remaining 29 cases, VA was more than 0.15 logMAR below the lower limit. There was no relationship between VA and cognitive domain tasks, although there was relationship between VA and motor domain tasks. Thirty-seven children performed at least one task in the cognitive set, 14 children did not perform any task in the motor set. Children with VA above the lower performed better in the cognitive and motor tasks. We concluded that ZIKV- infected children with CSZ were highly VA impaired which correlated with motor performance, but not with cognitive performance. Part of the children had VA within the normal limits and displayed better performance in the cognitive and motor set. Therefore, even if heavily impaired, most children had some degree of visual acuity and visual function.